Agricultural growth is the key to poverty alleviation in low-income developing countries - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (International Food Policy Research Institute, 1995)
Poverty is a rural phenomenon in most of the developing world, especially the low-income developing countries. The rural poor make up more than 75 percent of the poor in many Sub-Saharan African and Asian countries. Accelerated public investments are needed to facilitate agricultural and rural growth. These investments need to be supported by an enabling policy environment. This includes trade, macro, and sectoral policies that do not discriminate against agriculture, and policies that provide appropriate incentives for the sustainable management of natural resources.